DOMPET DIGITAL SEBAGAI ALAT ALTERNATIF PEMBAYARAN NON-TUNAI PADA UMKM DI DESA PADANGSAMBIAN - Claudya Trihanura Pranurti; Ida Nyoman Basmantra (Universitas Serang Raya, 2023)
The Covid-19 pandemic that is currently ravaging Indonesia, especially in Bali, has caused Micro, Small, and Medium Enterprises who had not previously used digital platforms as an alternate method of payment to do so. The existing lack of understanding among MSMEsplayers in Padangsambian village regarding the usage of digital payment systems would almost surely reduce customer interest in transacting with the items on sale. As a result of the issues, there will be educational outreach on the benefits of digital payment platforms for MSMEs through the usage of an e-wallet. The purpose of this socialization is to increase the knowledge of MSMEs owners so that they can take advantage of the e-wallet platform as an alternative digital payment tool in the midst of a pandemic, so as to increase the effectiveness and attractiveness of consumers in making transactions. The method used is to implement a communication strategy to the owners of Micro,Small and Medium Enterprises (MSMEs). The results of this socialization will help MSMEs in Padangsambian village to increase sales and become more competitive in the digital era.